2020
DOI: 10.3344/kjp.2020.33.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative duloxetine as part of a multimodal analgesia regime reduces postoperative pain in lumbar canal stenosis surgery: a randomized, triple blind, and placebo-controlled trial

Abstract: Background: Duloxetine is an antidepressant that is also useful in chronic neuropathic and central origin pain. In this study, the role of duloxetine in decreasing acute postoperative pain after lumbar canal stenosis surgery is explored. Methods: In this single center, triple blinded, and placebo-controlled trial, 96 patients were randomized for statistical analysis. The intervention group received oral duloxetine 30 mg once a day (OD) for 2 days before surgery, 60 mg OD from the day of surgery to the postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Analgesic drugs can be given through an epidural catheter after surgery, which is a safe and effective method for treating acute postoperative pain 3 . Studies 4,5 have shown that compared with the use of a single drug for postoperative analgesia, multimodal analgesia with different technologies can reduce the dose of opioids and have better analgesic effects. Ropivacaine is an amide‐type local anaesthetic, which has less central nervous system and cardiovascular toxicity, and has better delayed gaps on the sensory and motor nerve block 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Analgesic drugs can be given through an epidural catheter after surgery, which is a safe and effective method for treating acute postoperative pain 3 . Studies 4,5 have shown that compared with the use of a single drug for postoperative analgesia, multimodal analgesia with different technologies can reduce the dose of opioids and have better analgesic effects. Ropivacaine is an amide‐type local anaesthetic, which has less central nervous system and cardiovascular toxicity, and has better delayed gaps on the sensory and motor nerve block 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Govil et al found total morphine consumption up to 24 h was significantly decreased in the duloxetine group when used for a total duration of 7 days perioperatively. [ 12 ] But in the current study, we have used only a single dose of 60 mg duloxetine preoperatively, duloxetine has a mean plasma half-life of 12 h thus might not have had a significant effect on postoperative pain. Duloxetine, when used alone as single dose preoperatively, did not have a significant effect on reducing postoperative pain but when combined with dexamethasone had a significant reduction in requirements for rescue analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] There are many studies that have shown preoperative use and continued postoperative use of duloxetine for a few days to weeks has a significant effect on reducing postoperative pain and on reducing analgesic requirements in various surgical patients. [ 8 9 10 11 12 ] There is no literature available on the effect of single preoperative dose of duloxetine on postoperative pain following spinal anesthesia. In the present study, we hypothesized that a single dose of 60 mg duloxetine may reduce postoperative pain in patients undergoing abdominal hysterectomy under spinal anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…It is no exaggeration to say that the history of medicine derived from humans trying to reduce pain. In modern times, these efforts to lessen pain are summed up by the term "multimodal analgesia," which refers to a medical practice using diverse systemic medications with various mechanisms of actions [1,2] along with regional/peripheral block techniques [3].…”
Section: Introductionmentioning
confidence: 99%